Pola Kepemimpinan Sultanah Aceh dalam Pengembangan Ilmu Pengetahuan 1641-1699 M: The Leadership Pattern of the Sultanah of Aceh in the Development of Science 1641-1699 M - Subkhana Adzim Baqi; Aziz, Muhammad; Windari, Sri (Journal of Islamic History, 2022)
This study aims to determine the leadership pattern applied by the Sultanah of Aceh in the development of science from 1641-1699 AD. The method used in this study is the historical method. The election of Sultanah Aceh in its historical reflection experienced turbulence between groups who opposed the ascension to the throne of leadership from the Sultanah of Aceh. So that in its development, starting from the leadership of Sultanah Tajul Alam until the time of Kamalat Shah, the opponents (Wujudiyah) continued to try to overthrow Sultanah's leadership in the kingdom of Aceh Darussalam. The results of this study indicate that the leadership pattern of Sultanah Aceh in the development of science in the first period showed a significant development, until the fourth period. Although actually the sultanah as the queen had high authority, the Sultanah still held consultations with the royal advisor who was then held by a cleric, especially in determining an action or policy aimed at achieving progress towards the Aceh kingdom.